Memahami Penggunaan Pasal 12 UUD 1945 dalam Perspektif Legislative Model di Indonesia - Ayuni, Qurrata (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2025)
This article analyzes the application of Article 12 of the 1945 Constitution as the constitutional basis for the State of Emergency (Hukum Tata Negara Darurat) in Indonesia. The study is driven by the historical tendency to abuse emergency powers and the marginalization of the legislature’s role in declaring a state of danger. The main question addressed is: How can the provisions of Article 12 be understood and applied within the framework of the Legislative Model to ensure legislative involvement and oversight over presidential emergency powers? The purpose of this study is to explain how Article 12 of the 1945 Constitution can be interpreted within this framework to strengthen legislative oversight and provide a normative foundation for emergency law reform in Indonesia. This research employs a doctrinal method, using conceptual and statutory approaches. The findings show that Article 12 of the 1945 Constitution not only grants authority to the President but also mandates the involvement of the House of Representatives (DPR) in determining the conditions and consequences of an emergency through legislation. The conclusion highlights the urgent need to reform emergency-related regulations in line with Article 12 of the 1945 Constitution and to establish a clear mechanism for legislative oversight.AbstrakTulisan ini menganalisis penerapan Pasal 12 UUD 1945 sebagai dasar konstitusional dalam Hukum Tata Negara Darurat (HTN Darurat) di Indonesia. Kajian ini dilatarbelakangi oleh kecenderungan historis penyalahgunaan kewenangan darurat dan pengabaian peran legislatif dalam penetapan keadaan bahaya. Permasalahan utama yang dikaji adalah: Bagaimana pengaturan dalam Pasal 12 UUD 1945 dapat dipahami dan diterapkan dalam kerangka Legislatif Model guna menjamin keterlibatan dan pengawasan lembaga legislatif terhadap kewenangan darurat Presiden?Tujuan penulisan ini adalah untuk menjelaskan bagaimana Pasal 12 UUD 1945 dapat diinterpretasikan dalam kerangka tersebut, guna memperkuat peran pengawasan legislatif terhadap kewenangan darurat Presiden dan memberikan dasar pembaruan hukum kedaruratan di Indonesia. Metode penelitian yang digunakan adalah doktrinal dengan pendekatan konseptual dan perundang-undangan. Hasil kajian menunjukkan bahwa Pasal 12 UUD 1945 bukan sekadar memberi kewenangan kepada Presiden, tetapi juga mengatur keterlibatan DPR dalam menetapkan syarat dan akibat pelaksanaan keadaan darurat melalui undang-undang. Simpulan menekankan pentingnya pembaruan regulasi dengan karakter kedaruratan yang merujuk pada Pasal 12 UUD 1945 dan memperjelas mekanisme pengawasan legislatif.